Phase II study of oxaliplatin, fluorouracil, and folinic acid in locally advanced or metastatic gastric cancer patients - Louvet, C; André, T; Tigaud, J M; Gamelin, E; Douillard, J Y; Brunet, R; François, E; Jacob, J H; Levoir, D; Taamma, A; Rougier, P; Cvitkovic, E; et al. (Journal of clinical oncology, 2002)
To evaluate the efficacy and safety of an oxaliplatin, fluorouracil (5-FU), and folinic acid (FA) combination in patients with metastatic or advanced gastric cancer (M/AGC). Of the 54 eligible patients with measurable or assessable M/AGC, 53 received oxaliplatin 100 mg/m(2) and FA 400 mg/m(2) (2-hour intravenous infusion) followed by 5-FU bolus 400 mg/m(2) (10-minute infusion) and then 5-FU 3,000 mg/m(2) (46-hour continuous infusion) every 14 days. Patients (69% male, 31% female) had a median age of 61 years (range, 31 to 75 years), 89% had a performance status of 0 or 1, 70% had newly diagnosed disease, and 87% had metastatic disease. All had histologically confirmed adenocarcinoma. With a median of three involved organs, disease sites included the lymph nodes (67%), stomach (65%), and liver (61%). A median of 10 cycles per patient and 468 complete cycles were administered. Best responses in the 49 assessable patients were two complete responses and 20 partial responses, giving an overall best response rate of 44.9%. Eight patients underwent complementary treatment with curative intent (six with surgery and two with chemoradiotherapy). Median follow-up, time to progression, and overall survival were 18.6 months, 6.2 months, and 8.6 months, respectively. Grade 3/4 neutropenia, leukopenia, thrombocytopenia, and anemia occurred in 38%, 19%, 4%, and 11% of patients, respectively, and febrile neutropenia occurred in six patients (one episode each). Grade 3 peripheral neuropathy occurred in 21% of patients (oxaliplatin-specific scale). Seven patients withdrew because of treatment-related toxicity. This oxaliplatin/5-FU/FA regimen shows good efficacy and an acceptable safety profile in M/AGC patients, and may prove to be a suitable alternative regimen in this indication.